Using farmer decision-making profiles and managerial capacity as predictors of farm management and performance in Costa Rican dairy farms - Solano, C.; León, H.; Pérez, E.; Tole, L.; Fawcett, R.H.; Herrero, Mario (Elsevier, 2006)
This paper studies the impact of a series of biographical variables and decision-making profiles, representative of the managerial capacity of the farmer, on the management and performance of their farms. It integrates all the profiles representing farmer’s objectives, decision-making approaches and preferred information flows developed by Solano et al. [Solano, C.; León, H., Pérez, E., Herrero, M. 2001a Characterising objectives profiles of Costa Rican dairy farmers. Agricultural Systems 67, 153–179; 2001b, 181–199] and Solano et al. (2003). These profiles, along with some biographical variables and farm characteristics are then used as explanatory variables in a series of analyses of variance to evaluate the impact of these variables on the management and performance of farms. Management is characterised by variables derived from a factor analysis. Factors include: pasture management, nutritional and reproductive strategies, and aspects of animal health. Performance indicators include: milk yield per cow per day, milk yield per hectare per year, margin per cow per day, margin per ha per year, rate of return on working capital, and an efficiency parameter derived from a stochastic frontier production model. Results demonstrate significant relationships between managerial capacity and management approaches, and significant relationships between management approaches and performance of the farm. Limited effects of managerial variables on performance and efficiency are also found. Results are discussed in terms of their implications for future development of decision-support systems and in terms of technology transfer activities.